YURIDICAL STUDY ON CLIMATE CHANGE MITIGATION THROUGH FORESTRY MANAGEMENT BY THE LOCAL GOVERNMENT - Zunnuraeni Zunnuraeni; Fatahullah Fatahullah; Ahmad Zuhairi (Jurnal IUS Kajian Hukum dan Keadilan, 2018)
The authority of the local government to regulate and manage its own household affair including forestry management is a challenge in the implementation of climate change mitigation. However there have been some amendment on forest sector in Act regarding Local Government. These change would impact to the authority of local government including climate change mitigation through forestry management. Therefore, aim of this study is to know whether the local government act may supported nor hampered the implementation of climate change mitigation trough forestry management. This study is a normative study with legislative approach and conceptual approach. Techniques of data collection is literature study. It is then analyze qualitatively. Result of the research is that amendment on rule over forest management in Act Number 23 year 2014 Regarding Local Government that gives the central government large authority concerning natural resources resulting to definite authority of local government concerning forest management including climate change mitigation. This may lead to the possibility of uneffective implementation on climate change mitigation by local government.